Accuracy of Preoperative Scoring Systems for the Prognostication and Treatment of Patients with Spinal Metastases. (15th August 2017) - Hibberd, Catherine S.; Quan, Gerald M. Y.
Abstract : Background . In patients with spinal metastatic disease, survival prognosis is a key consideration in selection for surgery and determining the extent of treatment. Individual survival prediction however remains difficult. We sought to validate the prognostic accuracy of seven preoperative scoring systems. Methods . 61 patients surgically treated for spinal metastases were retrospectively reviewed. Preoperative scores were calculated for Tokuhashi, Revised Tokuhashi, Bauer, Modified Bauer, Sioutos, Tomita, and van der Linden scoring systems. Prognostic value was determined by comparison of predicted and actual survival. Results . The Revised Tokuhashi and Modified Bauer scoring systems had the best survival predictive accuracy. Rate of agreement for survival prognosis was the greatest for the Modified Bauer score. There was a significant difference in survival of the prognostic groups for all but the van der Linden score, being most significant for the Revised Tokuhashi, Bauer, Modified Bauer, and Tomita scoring systems (p ≤ 0.001 ). Conclusion. Overall, the scoring systems are accurate at differentiating patients into short-, intermediate-, and long-term survivors. More precise prediction of actual survival is limited and the decision for or against surgery should never be based on survival prognostication alone but should take into account symptoms such as neurological deficit or pain from pathological fracture and instability.